2017
DOI: 10.1093/toxsci/kfw268
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-mediated activation of the HSP90/HSF1 pathway regulated by reactive persulfides/polysulfides

Abstract: Cadmium is an environmental electrophile that modifies reactive thiols in proteins, indicating that this heavy metal may modulate redox-signal transduction pathways. The current consensus is that reactive persulfides and polysulfides produced by cystathionine c-lyase (CSE) and cystathionine b-synthase are highly nucleophilic and thus cadmium may be captured by these reactive sulfur species. It has previously been found that electrophile-mediated covalent modifications of the heat shock protein (HSP) are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…2015b), suggesting that CSE participates in diminishment of environmental electrophile-mediated toxicity through formation of sulfur adducts. Although we have reported that knockdown or deletion of CSE enhances Cd-mediated toxicity both in vitro (Shinkai et al. 2017) and in vivo (Akiyama et al.…”
Section: Introductionmentioning
confidence: 99%
“…2015b), suggesting that CSE participates in diminishment of environmental electrophile-mediated toxicity through formation of sulfur adducts. Although we have reported that knockdown or deletion of CSE enhances Cd-mediated toxicity both in vitro (Shinkai et al. 2017) and in vivo (Akiyama et al.…”
Section: Introductionmentioning
confidence: 99%
“…Abiko and coworkers [60] found that detoxification of methyl mercury can occur via interaction with H 2 S, hydropersulfides and polysulfides. Similarly, Cd 2+ toxicity can also be abated by the presence of hydropersulfides [61]. Importantly, Zn 2+ and Cd 2+ are chemically and biochemically similar in that they both readily bind thiol proteins and indeed a facet of Cd 2+ toxicity is thought to involve interference with Zn 2+ homeostasis [62].…”
Section: Are Hydropersulfides Involved In Metal/ Metalloprotein Biology?mentioning
confidence: 99%
“…The metabolite analysis of wild-type (WT) and CSE knockout (KO) mice exposed to MeHg showed that (MeHg) 2 S was present at significant levels in various WT mouse tissues, but not at appreciable levels in CSE KO mouse tissues [79], suggesting that CSE is a critical enzyme involved in capturing xenobiotic electrophiles through formation of sulfur adducts in vivo. Furthermore, knockdown of CSE enhanced Cd-induced cytotoxicity, whereas overexpression of CSE protected cells from this electrophile-induced cytotoxicity [83]. In vivo studies have shown that CSE deletion in mice causes increased sensitivity to acetaminophen-induced hepatotoxicity, Cd-induced hepatotoxicity and MeHg-induced toxicity [20,77,84].…”
Section: Protective Function Of Rss Against Electrophilic Stressmentioning
confidence: 99%